2024
DOI: 10.3390/polym16050709
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Overview of Magnetic Composites for Water Decontamination

Adelina-Gabriela Niculescu,
Bogdan Mihaiescu,
Dan Mihaiescu
et al.

Abstract: Water contamination by harmful organic and inorganic compounds seriously burdens human health and aquatic life. A series of conventional water purification methods can be employed, yet they come with certain disadvantages, including resulting sludge or solid waste, incomplete treatment process, and high costs. To overcome these limitations, attention has been drawn to nanotechnology for fabricating better-performing adsorbents for contaminant removal. In particular, magnetic nanostructures hold promise for wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 298 publications
0
3
0
Order By: Relevance
“…Additionally, the use of advanced characterization techniques allows the optimization of aerogel-based thin films toward obtaining more performant adsorbent materials. Such gel structures can be employed for the removal of organic contaminants (e.g., organic dyes, pesticides, polycyclic aromatic hydrocarbons, organic solvents, and oils) and different heavy metal ions (e.g., Cr(III), Cr(IV), As(V), Cd(II), Cu(II), and Pb(II)) [ 65 , 66 , 67 ]. Moreover, interesting studies have revealed the potential of aerogels for gas adsorption, opening the door for air purification [ 68 , 69 , 70 ] and CO 2 conversion applications [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the use of advanced characterization techniques allows the optimization of aerogel-based thin films toward obtaining more performant adsorbent materials. Such gel structures can be employed for the removal of organic contaminants (e.g., organic dyes, pesticides, polycyclic aromatic hydrocarbons, organic solvents, and oils) and different heavy metal ions (e.g., Cr(III), Cr(IV), As(V), Cd(II), Cu(II), and Pb(II)) [ 65 , 66 , 67 ]. Moreover, interesting studies have revealed the potential of aerogels for gas adsorption, opening the door for air purification [ 68 , 69 , 70 ] and CO 2 conversion applications [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surface-functionalized Fe 3 O 4 NPs have also been recognized as valuable materials for water decontamination purposes, acting as effective nanoadsorbents for various pollutants and enabling facile magnetic separation from aqueous samples after treatment [ 2 ]. Specifically, prior studies reported the successful utilization of citric acid-coated Fe 3 O 4 NPs for crystal violet adsorption [ 54 ], aminochitosan-coated Fe 3 O 4 NPs for diclofenac sodium adsorption [ 67 ], polyaniline-coated Fe 3 O 4 NPs with for the adsorption of polycyclic aromatic hydrocarbons [ 68 ], silica-coated Fe 3 O 4 NPs for Pb(II) adsorption [ 69 ], and [ 68 ] salicylic acid-coated Fe 3 O 4 NPs for Cd(II) adsorption [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic nanoparticles, which are unique and versatile materials, are broadly perceived for their important roles in various applications such as medicine, biotechnology, agriculture, engineering, and the environment [ 1 , 2 , 3 , 4 , 5 ]. These particles, usually smaller than 100 nm, obtain magnetic characteristics attributed to their tiny size and distinct compositions, including superparamagnetism and high magnetic susceptibility [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%